Students' Mathematical Critical Thinking Ability in Term of Self-Confidence in CORE Model Learning with Open-Ended Approach - Sari, Yunita Eka; Safaatullah, Muh. Fajar (Universitas Negeri Semarang, 2024)
The study aimed to: (1) to examine the effect of grade VII students' self-confidence on their the mathematical critical thinking ability of grade VII students in the CORE learning model with an open-ended approach achieved classical completeness; (2) to examine the mathematical critical thinking ability of grade VII students in the CORE learning model with an open-ended approach achieved classical completeness; (3) to examine the average mathematical critical thinking ability of grade VII students in the CORE model with an open-ended approach to that in the PBL model; and (4) to describe the mathematical critical thinking ability of grade VII students based on their self-confidence levels in the CORE learning model with an open-ended approach. This research employed a mixed-methods approach with a sequential explanatory design. The sampling technique used was simple random sampling, while subject selection applied purposive sampling. Data were collected through tests of mathematical critical thinking ability, self-confidence questionnaires, and interviews. The results showed: (1) self-confidence positively influenced mathematical critical thinking ability by 39.1%; (2) the mathematical critical thinking ability of grade VII students in the CORE model with an open-ended approach reached 81.25% classical completeness; (3) the average mathematical critical thinking ability in the CORE model was better than in the PBL model; (4) students with high self-confidence demonstrated all four stages of mathematical critical thinking (clarification, assessment, inference, and strategy/tactics), students with medium self-confidence fulfilled two stages (clarification and assessment), and students with low self-confidence achieved only the clarification stage.